Intensification of Very Wet Monsoon Seasons in India Under Global Warming. Issue 15 (10th August 2022) - Katzenberger, Anja; Levermann, Anders; Schewe, Jacob; Pongratz, Julia
Abstract: Rainfall‐intense summer monsoon seasons on the Indian subcontinent that are exceeding long‐term averages cause widespread floods and landslides. Here we show that the latest generation of coupled climate models robustly project an intensification of very rainfall‐intense seasons (June–September). Under the shared socioeconomic pathway SSP5‐8.5, very wet monsoon seasons as observed in only 5 years in the period 1965–2015 are projected to occur 8 times more often in 2050–2100 in the multi‐model average. Under SSP2‐4.5, these seasons become only a factor of 6 times more frequent, showing that even modest efforts to mitigate climate change can have a strong impact on the frequency of very strong rainfall seasons. Besides, we find that the increasing risk of extreme seasonal rainfall is accompanied by a shift from days with light rainfall to days with moderate or heavy rainfall. Additionally, the number of wet days is projected to increase. Plain Language Summary: The South Asian monsoon affects the life of more than one billion people. In the past, summer monsoon seasons (June–September) with very intense rainfall have been associated with widespread floods and an increased number of landslides. Here, we set the focus on the question how the probability of these very wet monsoon seasons will change in the 21st century under climate change. For this purpose, we use the latest generation of climate models with improved performance regarding the Indian monsoon as well as reduced uncertainties compared to the previous model generation. Under the strongest emission scenario, very wet monsoon seasons that used to be observed in 5 out of 50 years in the period 1965–2015 are projected to occur 8 times more frequently in 2050–2100 on multi‐model average. With modest mitigation efforts, this is reduced to a factor of 6 in the future period. Besides, this increase in frequency and intensity of extreme monsoon seasons is accompanied by a shift from days with light rainfall to days with moderate or heavy rainfall. Additionally, the number of wet days is projected to increase. The particular character of the change depends on the determination of humankind to reduce carbon emissions and implement mitigation measures. Key Points: The latest generation of coupled climate models project an increase in severity and frequency of very wet Indian summer monsoon seasons Very wet monsoon seasons are projected to occur 8 times more often in 2050–2100 compared to 1965–2015 under unabated climate change On the subseasonal scale, there is a shift from days with light rainfall to days with moderate or heavy rainfall